Effect of rape seed oil quality on biodiesel composition - Skopal, František; Machek, Jaroslav; Komers, Karel (Univerzita Pardubice, 2007)
The methanolysis of rape seed oil catalyzed by KOH has been studied from the standpoint of the dependences of the acid value (neutralisation number) and concentration of unreacted oil (as sum of glycerides) in the final mixture of methyl esters of fatty acids on the oil (biodiesel) on the initial KOH concentration in methanol and on the acid value and water content of the used oil.
Keywords: řepkový olej; Bionafta; složení